2010
DOI: 10.4104/pcrj.2010.00041
|View full text |Cite
|
Sign up to set email alerts
|

Herbal interventions for chronic asthma in adults and children: a systematic review and meta-analysis

Abstract: Aims: To assess the efficacy of herb and plant extracts in the management of asthma.Method: Systematic review and meta-analysis. Multiple database searches identified randomised placebo controlled trials of herbal interventions reporting at least one primary outcome measure. Where possible data were combined for meta-analysis. Primary outcome measures were lung function, exacerbations and reduction in corticosteroid use. Secondary outcome measures were symptoms and symptom scores, use of reliever medications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 33 publications
(117 reference statements)
0
38
0
4
Order By: Relevance
“…Due to the small sample size and poor methodology, there were no clear recommendations in applying TCM for the treatment of asthma [24,25,26], although some studies reported promising effects [27,28,29,30,31]. The employment of Chinese herbal preparations resulted in beneficial improvements in the pulmonary function and relieved asthma symptoms [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size and poor methodology, there were no clear recommendations in applying TCM for the treatment of asthma [24,25,26], although some studies reported promising effects [27,28,29,30,31]. The employment of Chinese herbal preparations resulted in beneficial improvements in the pulmonary function and relieved asthma symptoms [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund des geringen Stichprobenumfangs und der mangelhaften Methodik wurden keine klaren Empfehlungen fĂŒr die Anwendung der TCM zur Behandlung von Asthma ausgesprochen [24,25,26], obwohl einige Studien von vielversprechenden Effekten berichten [27,28,29,30,31]. Der Einsatz chinesischer PflanzenprĂ€parate bewirkte Verbesserungen der Lungenfunktion und eine Linderung der Asthmasymptomatik [27,28,29].…”
Section: Diskussionunclassified
“…Most studies that have been carried out are in cases of adults and children with asthma. A review of herbal preparation studies in asthma identified 26 trials of 20 different herbal preparations, and the majority of the studies reported no significant differences in measure of lung function or steroid dosage [12]. A few smaller studies reported improvement in forced expiratory volume in one second (FEV1) or airway hyper-responsiveness for herbal remedies such as Ding Chuan Tang [13], Boswellia [14], TJ-96-Saiboku-to [15], and Tylophoraindica [16].…”
Section: Dietary Supplementsmentioning
confidence: 99%